Health literacy and the voluntary adoption of the new normal in COVID-19: The case of Japan - John W. Cheng; Hitoshi Mitomo; Artima Kamplean; Yongkyoung Seo (International Telecommunications Society (ITS), 2022)
This study quantitatively examines factors behind the Japanese public's high voluntary compliance with the government's 'new normal' advice during COVID-19 from both sociocultural and health communication perspectives. Using survey data collected from 3,100 adults in Japan in October 2021, it is found that social coercion increases people's willingness to comply with government advice while belief in COVID-19 conspiracy theories has the opposite effect. In parallel, it is found that perceived efficacy of the new normal practices also increases the willingness to comply with government advice, and the effect is strengthened by health literacy.
Keywords: 330